DDIT4 Novel Mutations in Pancreatic Cancer. (3rd May 2021) - Ding, Fadian; Hong, Xiaoping; Fan, Xiangqun; Huang, Shirong; Lian, Wei; Chen, Xingting; Liu, Qicai; Chen, Youting; Gao, Feng
Abstract : Pancreatic cancer is one of the most common malignancies worldwide. This study is aimed at searching the possible genetic mutations and the value of novel gene mutation in the DNA damage-inducible transcript 4 (DDIT4) and signaling pathway in pancreatic cancer. Polymerase chain reaction (PCR) was performed to amplify the DNA sequences of DDIT4 from patients with pancreatic ductal adenocarcinoma. In addition, we used IHC to detect the expression level of DDIT4 in patients with pancreatic cancer in different types of gene mutation. Double-labeled immunofluorescence was employed to explore the expression levels of DDIT4/LC3 and their potential correlation. Our work indicated the two novel stable gene mutations in DDIT4 mRNA 3 ′ -untranslated region (m.990 U>A and m.1246 C>U). Thirteen samples were found to have mutation in the DDIT4 3 ′ -untranslated regions (UTR). To further verify the influence of gene mutation on protein expression, we performed immunohistochemistry on different gene mutation types, and we found a correlation between DDIT4 expression and gene mutation, which is accompanied by nuclear staining deepening. In order to further discuss the clinical value of DDIT4 gene mutation, immunofluorescence suggested that the expression of DDIT4 colocated with LC3; thus, we speculated that DDIT4 mutation may be involved in autophagy in pancreatic cancer cell. In this study, we found mutation in the 3 ′ -UTR region of DDIT4, which may be associated with DDIT4 expression and tumor autophagy in pancreatic cancer tissues.